2014
DOI: 10.2355/isijinternational.54.1195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interfacial Properties between Molten Iron and Alumina on Neck Growth of Alumina Balls at Sintering in Molten Iron

Abstract: The effects of interfacial properties such as interfacial tension and wettability on the adhesion, agglomeration, and coalescence of inclusions on the immersion nozzle in a continuous casting process have not yet been evaluated quantitatively. In the present work, we focused on the neck growth of alumina balls at sintering because the adhesion, agglomeration, and coalescence of inclusions are regarded as being the consequence of sintering of oxides. We compared the neck growth of alumina balls at sintering in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…A force acts on two liquid Fe particles by pressing them toward each other to facilitate their aggregation, which is advantageous for the coarsening of liquid Fe. Nakamoto et al 18) reported that when the liquid did not wet the particle, the liquid was extracted from the gap between the particles by capillary action, and the aggregation of the particles was promoted by capillary action. Assuming that the capillary action in the gap between the particles is equal to those between the two plates, the capillary force occurring between the spherical particle and the liquid is expressed as eq.…”
Section: Effect Of Tio 2 On Recovery Of Reduced Metallic Fe In Regoli...mentioning
confidence: 99%
“…A force acts on two liquid Fe particles by pressing them toward each other to facilitate their aggregation, which is advantageous for the coarsening of liquid Fe. Nakamoto et al 18) reported that when the liquid did not wet the particle, the liquid was extracted from the gap between the particles by capillary action, and the aggregation of the particles was promoted by capillary action. Assuming that the capillary action in the gap between the particles is equal to those between the two plates, the capillary force occurring between the spherical particle and the liquid is expressed as eq.…”
Section: Effect Of Tio 2 On Recovery Of Reduced Metallic Fe In Regoli...mentioning
confidence: 99%
“…非金属介在物は,鋼の内外の欠陥となることで強度や耐 疲労性の低下などの品質低下を引き起こすため,高清浄鋼 の溶製技術の発展が求められている 1,2) 3,4) 。 非金属介在物の除去にあたっては,介在物同士の衝突お よび凝集合体を促進し,浮上分離に有利な粗大介在物とす ることが有効である 2,5) 。介在物の凝集合体の制御および 見積りには,界面エネルギーや接触角といった介在物 -溶 鋼間の濡れ性を把握することが重要である 2,6)…”
Section: 緒言unclassified
“…Therefore, to manipulate the second angle there may be two ways: the first is to use CaO as a surface cover which would decrease it by liquifying the alumina inclusions and decreasing the contact angle between the melt and the calcium aluminate inclusion or to use a conventional AG material with a special treatment. The first approach leads to high wearing rates of the refractory due to the formation of liquid aluminates, [27,28] leaving just the option of using more elaborated conventional AG materials. It would be apparent that the only way to achieve that is to manufacture a nozzle material with the smoothest internal surface.…”
Section: Temperaturementioning
confidence: 99%